2012
DOI: 10.1590/s0100-40422012001000012
|View full text |Cite
|
Sign up to set email alerts
|

Multi-component quantitation of loratadine, pseudoephedrine and paracetamol in plasma and pharmaceutical formulations with liquid chromatography-tandem mass spectrometry utilizing a monolithic column

Abstract: Recebido em 16/2/12; aceito em 5/7/12; publicado na web em 25/9/12The purpose of this study was to develop a rapid, simple and sensitive quantitation method for pseudoephedrine (PSE), paracetamol (PAR) and loratadine (LOR) in plasma and pharmaceuticals using liquid chromatography-tandem mass spectrometry with a monolithic column. Separation was achieved using a gradient composition of methanol-0.1% formic acid at a flow rate of 1.0 mL min -1. Mass spectral transitions were recorded in SRM mode. System validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In our previous reported studies, we demonstrated various analytical methods using monolithic columns (Abro, Memon, Bhanger, Mahesar, et al 2011;Abro, Memon, Bhanger, Perveen, and Kandhro 2012;Abro, Memon, Bhanger, Perveen, and Panhwar 2012). To continue this work, the objective of the present study was to develop a method that can be employed in routine analysis for diagnostic purposes of these vitamins.…”
Section: Introductionmentioning
confidence: 87%
“…In our previous reported studies, we demonstrated various analytical methods using monolithic columns (Abro, Memon, Bhanger, Mahesar, et al 2011;Abro, Memon, Bhanger, Perveen, and Kandhro 2012;Abro, Memon, Bhanger, Perveen, and Panhwar 2012). To continue this work, the objective of the present study was to develop a method that can be employed in routine analysis for diagnostic purposes of these vitamins.…”
Section: Introductionmentioning
confidence: 87%
“…THCA and its glucuronide conjugate are major urinary cannabinoid metabolites and the WADA threshold for THCA is 150 ng/ml. Dilute-and-shoot method development and validation for LC-MS/MS to measure urinary THCA has been described in the literature [10][11][12] and this approach permitted more rapid sample preparation with fewer steps prior to LC-MS/ THCA 150 ng/ml 15 ng/ml 10 180 ng/ml [10][11][12][13][14][15][16][17][18][19][20][21] Salbutamol 1.0 μg/ml 0.1 μg/ml 10 1.2 μg/ml [22][23][24] Formoterol 40 ng/ml 6.0 ng/ml 15 50 ng/ml [10,[25][26][27] Glycerol 4.3 mg/ml 0.65 mg/ml 15 5.3 mg/ml [28][29][30] Morphine 1.0 μg/ml 0.15 μg/ml 15 1.3 μg/ml [31][32][33][34][35][36][37][38][39][40][41] Cathine 5.0 μg/ml 0.5 μg/ml 10 6.0 μg/ml [22] Ephedrine 10 μg/ml 0.5 μg/ml 5 11 μg/ml [42][43][44][45][46][47][48][49]…”
Section: Quantification Of Banned Substances With and Without Thresholdsmentioning
confidence: 99%
“…To achieve baseline chromatographic separation of pseudoephedrine and its metabolite, norpseudoephedrine, which are ephedrine and norephedrine diastereomers, respectively, only one dilution step is needed for LC-MS or LC-MS/MS [22,42,43]. For plasma and serum samples, protein precipitation requires dilution with methanol [44] or acetonitrile [45,46,49], or LLE [47,48]. RPLC is a method of choice for urine [22,43,50], plasma and serum ephedrine separations [43][44][45]49].…”
Section: Morphinementioning
confidence: 99%
See 1 more Smart Citation
“…It is a major component in numerous cold and flu preparations also in combination with nonsteroidal anti‐inflammatory drugs and opioid analgesics (Sweetman, ). Surveying the literature revealed that PAR was determined in biological fluids either individually or in combination with other drugs by various analytical methods (Abro, Memon, Bhanger, Perveen, & Kandhro, ; Celma, Allue, Prunonosa, Peraire, & Obach, ; Farid & Abdelaleem, ; Gicquel, Aubert, Lepage, Fromenty, & Morel, ; Hairin et al, ; Hewavitharana, Lee, Dawson, Markovich, & Shaw, ; Li et al, ; Liao et al, ; Locatelli et al, ; Lou, Yuan, Ruan, & Jiang, ; Ophelia, Sherry, & Moses, ; Trettin et al, ; Zhu, Ding, Guo, Yang, & Wen, ).…”
Section: Introductionmentioning
confidence: 99%